On biogeochemistry and water quality of river canals in Northern France subject to daily sediment resuspension due to intense boating activities. (February 2015) - Prygiel, E.; Superville, P.-J.; Dumoulin, D.; Lizon, F.; Prygiel, J.; Billon, G.
Abstract: In Northern France, channelized rivers facilitate greatly the waterway transport that should still increase in the coming years to replace as much as possible the road traffic, considered as a heavier source of pollution. These rivers are now subjected to the good potential status objectives required by the Water Framework Directive. The impact of the recurrent resuspension by the current boat traffic of polluted sediments (due to strong historical pollution) on the water quality is the main concern of this work. Our study reveals that the navigation seems to play a limited role on the enrichment of the water columns by dissolved metals and phosphorus, as well as on the oxygenation of surface waters. Conversely, the cycling of the phytoplankton over the year appears to partly control the physico-chemical and chemical evolutions of the overlying waters. Highlights: In river canals boating results in the daily resuspension of polluted sediments. Chemical indexes indicate that metals should be well trapped in the sediments. Polluted sediments in Cd and Pb may only slightly enrich the river waters. Daily boating activity results in the scavenging of dissolved phosphorus. Phytoplanktonic biomass and seasonal effects partly control the water quality. Abstract : Polluted sediments resuspension in river canals by daily boat traffic seems to play a limited role on the enrichment of the water columns by dissolved metals and phosphorus.